Delegated Proof of Reputation Consensus Mechanism for Blockchain-Enabled Distributed Carbon Emission Trading System - Hu, Z. (Institute of Electrical and Electronics Engineers Inc., 2021)
10.1109/ACCESS.2020.3041689